1966
DOI: 10.1097/00000658-196602000-00013
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Technic for Vascular Isolation of the Liver

Abstract: of hepatic vascular exclusion for extensive liver resection. The American Jourt.l of Surgery; 163: 602-605. Hepatic vascular exclusion, which includes clamping of the portal pedicle along with the inferior vena cava below and above the liver, may be a useful procedure for resection of liver tumors close to the hepatic veins or the vena cava that are usually considered unresectable by conventional techniques. Since complete caval exclusion is the key to good hemodynamic tolerance and a bloodless transection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
9

Year Published

1968
1968
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(110 citation statements)
references
References 16 publications
2
97
0
9
Order By: Relevance
“…More extensive involvement of the IVC requires the use of a patch or segmental resection with graft replacement. In such cases, TVE may be used [6][7][8][9] . This may be achieved by applying vascular clamps to the IVC below and above the liver, with concomitant interruption of hepatic blood inflow using a Pringle maneuver [10] .…”
Section: Discussionmentioning
confidence: 99%
“…More extensive involvement of the IVC requires the use of a patch or segmental resection with graft replacement. In such cases, TVE may be used [6][7][8][9] . This may be achieved by applying vascular clamps to the IVC below and above the liver, with concomitant interruption of hepatic blood inflow using a Pringle maneuver [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Heneay at al. [12] were the first who described the total hepatic vascular exclusion (THVE). It combines the control of vascular inflow and outflow and vascular occlusion of the lower and upper part of v. cava inferior.…”
Section: Discussionmentioning
confidence: 99%
“…Heaney et al (26) first described the vascular isolation of the liver and demonstrated the efficacy of this technique in elective hepatic resections.…”
Section: Discussionmentioning
confidence: 99%